2013
DOI: 10.2147/ijwh.s53652
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a modified version of the applied relaxation technique in treatment of perimenopausal and postmenopausal symptoms

Abstract: BackgroundAwareness of the risks associated with hormone therapy for menopausal symptoms has sparked a global decline in this treatment. Alternative treatments to relieve menopausal symptoms are therefore required. The applied relaxation (AR) technique has proven to be successful for symptom amelioration, but requires participation in 12 weekly classes. The purpose of this study was to determine the effectiveness of a modified relaxation version (MR) of AR for treatment of hot flashes, night sweats, and sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…11 An RCT of 187 symptomatic menopausal women found that clinical hypnosis was associated with a 74.2% reduction in hot flushes, compared with a 17.1% reduction in women randomized to structured attention control (P < 0.001). 12 The effectiveness of acupuncture, 13 exercise, 14 yoga, 15 paced respiration, 16 relaxation training, 17 and mindfulness-based stress reduction 18 has not been established.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…11 An RCT of 187 symptomatic menopausal women found that clinical hypnosis was associated with a 74.2% reduction in hot flushes, compared with a 17.1% reduction in women randomized to structured attention control (P < 0.001). 12 The effectiveness of acupuncture, 13 exercise, 14 yoga, 15 paced respiration, 16 relaxation training, 17 and mindfulness-based stress reduction 18 has not been established.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%
“…[9] Relaxation techniques like paced respiration (slow deep breathing that uses the diaphragm for inhalation and exhalation) and muscle relaxation were effective for the relief of symptoms, hot flashes, night sweats and sleep disturbance. [10] Biofeedback Type of mind-body technique which involves control of some of the body's functions like heart rate, respiration, breathing and skin temperature. It relaxes muscles and eases stress.…”
Section: Complementary and Alternative Medicine For Menopausal Sympto...mentioning
confidence: 99%